ANALISIS PENGARUH VALUE PROPOSITION, PARASOCIAL RELATIONSHIP, CHATBOT, DAN FITUR VIRTUAL TRY-ON TERHADAP KEPUTUSAN PEMBELIAN GENERASI Z PADA PRODUK FASHION BAJU DI TIKTOK SHOP: KONTRIBUSI TERHADAP PERTUMBUHAN EKONOMI DAN PENCAPAIAN SDGS - Selvi Puspita Armanti; Ratna Listiana Dewanti (Journal Economics Technology And Entrepreneur, 2026)
This study aims to analyze the influence of value proposition parasocial relationship, chatbots, and the virtual try-on feature on Generation Z’s purchase decisions for fashion apparel products on TikTok Shop, as well as their contribution to economic growth and the achievement of the SDGs. This study employs a quantitative approach using a survey method involving 100 Generation Z respondents. Data analysis was conducted using IBM SPSS software version 27. The results show that, partially, value proposition, chatbots, and the virtual try-on feature have a positive and significant effect on consumer purchase decisions. In contrast, parasocial relationship does not have a significant partial effect on purchase decisions. However, simultaneo usly, value proposition, parasocial relationship, chatbots, and the virtu al try-on feature have a positive and significant effect on purchase decisions. These findings provide implications for fashion apparel MS MEs on TikTok Shop to optimize their digital marketing strategies thro ugh strengthening value proposition, enhancing parasocial relations hips, utilizing chatbots, and adopting the virtual try-on feature.